Histochemistry of Anaerobic Glycolysis in Meat Animals - Swatland, Howard J. (European Journal of Applied Sciences, 2025)
This review explains how pH measurements of pork and beef are dominated by the post mortem metabolism of one histochemical type of myofibre with alkaline myosin ATPase (fast contraction) and few mitochondria (an anaerobic specialization). Using glycogenolysis to identify the source of the lactic acid that acidifies muscles post mortem, these myofibres are involved in a variety of commercially important phenomena, from PSE (pale, soft, exudative) pork to electrical stimulation of beef to increase productivity.